Surgical Treatment of a Tuberculous Abscess of the Chest Wall - Keum, Dong-Yoon (Korean Society for Thoracic and Cardiovascular Surgery, 2012)
BACKGROUND: Tuberculous abscess of the chest wall is a very rare disease. Few articles have reported on it and those that have enrolled few patients. To determine the characteristics of this disease and to suggest an optimal treatment strategy, we reviewed patients treated by surgical management. MATERIALS AND METHODS: Between October 1981 and December 2009, 68 patients treated by surgical management for a tuberculous abscess of the chest wall were reviewed retrospectively. RESULTS: Of 33 men and 35 women, 31 patients had a current or previous history of tuberculosis. The main complaints were chest pain, a palpable mass, pus discharge, and coughing. A preoperative bacteriologic diagnosis was performed in 12 patients. Abscess excision was performed in 54 cases, abscess cavity excision and partial rib resection in 13, and abscess excision and partial sternum and clavicle excision in 1 case. Postoperative wound infection was noted in 16 patients and a secondary operation was performed in 1 patient. Recurrence occurred in 5 patients (7.35%). Reoperation with abscess excision and partial rib resection was performed in all of the 5 cases. CONCLUSION: Complete excision of the abscess and primary closure of the wound with obliteration of space would decrease postoperative complications. Anti-tuberculosis medication may reduce the chance of recurrence.